Aspects of Cultural Intelligence as Enablers in Expatriate Adjustment : Perceptions of Finnish expatriates - Viitasalo, Julia (My University, 2018)
The ability to communicate, work, and live with and amongst cultural differences has become the key characteristic for successful individuals and organizations in the global millennium. Therefore, the need to determine the capabilities that make some individuals successful in cross-cultural contexts has received a lot of interest. One of the theoretical concepts that has gained a lot of interest as a determinant of expartiate cross-cultural capabilities is the theory of cultural intelligence (Earley & Ang 2003). Research for cultural intelligence has enabled the realization that the ability to work across cultural borders is an individual cross-cultural capability. One of the main assumptions in the theoretical framework used is the fact that expatriates who utilize aspects of cultural intelligence are able to function effectively in and adjust to cross-cultural environments. The purpose of this thesis is to examine how expatriates utilize the different aspects of cultural intelligence as enablers of cross-cultural adjustment. In this thesis, the phenomenon is studied form the perspective of Finnish expatriates. The empirical data was collected through expert interviews with Finnish expatriates all from the same public organization currently working in assignment abroad. A total of five semi-structured interviews were conducted. Thematic analysis was used to analyze, categorize, and interpret the empirical data due to the exploratory and descriptive nature of the study and the aim to provide in-depth subjective considerations on the research phenomena in the specific context. The findings of this thesis support the fact that aspects from all cultural intelligence facets, including cultural strategic thinking, behavioral cultural intelligence and motivational cultural intelligence, are utilized by expatriates as enablers in cross-cultural adjustment. All the different aspects are needed in order for the expatriates to adjust their thinking and behavior according to the cultural setting they are in. Finnish expatriates utilize the aspects of cultural intelligence to understand the host culture, strategize and act upon the knowledge they have, as well as keep themselves motivated and interested to learn about the culture and to adjust. This thesis highlights the value of the aspects of cultural intelligence as critical competencies in today's globalized world. The central findings of this thesis imply that individuals are not able to succeed in another culture, unless they have the capabilities to decipher, understand and internalize the cultural meanings and framework. Furthermore, this study highlights the capability to form local networks and reference groups as essential for adjustment, as cultural intelligence is enhanced through social reflection and interaction.
Keywords: cultural intelligence, cross-cultural adjustment, adjustment process, expatriate, Finnish